Strategic Thinking on SDN - Leping Wei (Dianxin kexue, 2015)
Comprehensive analysis on global and disruptive impacts to telecom industry due to SDN development from strategic vision was made. It was started from the introduction on meaning and similarity and difference of SDN and NFV. Comparison on basic characteristics between telecom industry and information industry was made and exploration and lessons of telecom industry before SDN were analyzed. In the following part, fundamental problems of existing networks and major driving forces for SDN development were investigated. Next basic characteristics and five key values of SDN and application prospect were described. Finally major challenges for SDN development were presented and key points of thinking on SDN from strategic vision were summarized.